2015
DOI: 10.1007/s13277-015-4715-1
|View full text |Cite
|
Sign up to set email alerts
|

CUL4A expression in pediatric osteosarcoma tissues and its effect on cell growth in osteosarcoma cells

Abstract: Osteosarcoma (OS) is the most common bone malignancy in the pediatric population, and it comprises about 3 % of all pediatric tumors. Aberrant expression of the Cullin 4A (CUL4A) is found in many tumor types, but the role of CUL4A in OS progression remains largely unknown. The aim of this study was to investigate the expression and function of CUL4A in OS. CUL4A expression was detected in 30 samples of surgically resected OS and matched tumor-adjacent tissues using quantitative reverse transcription polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Lung cancer initiation and progression (transgenic overexpression of Cul4a) [89][90][91] ;Resistant to UV-induced skin carcinogenesis (skin-specific knockout of Cul4a) 55 Overexpressed in multiple myeloma 310 , cholangiocarcinoma 113,114 , gastric cancer [102][103][104] , colorectal cancer 104,[107][108][109] , ovarian cancer 104,112,311 , lung cancer 93,110,111 , breast cancer [104][105][106] , osteosarcoma 312,313 , hepatocellular cancer 117,314 , malignant pleural mesothelioma 315,316 , pituitary adenoma 317 , prostate cancer 318 CUL4B Oncogenic Spontaneous development of liver cancer (transgenic overexpression of Cul4b) 92 Overexpressed in cholangiocarcinoma 120 , pancreatic carcinoma 119 , lung cancer 93 • 118 , colorectal cancer 115,116 , glioma 319 , liver cancer 122 , cervical cancer 121 290,325 HBx Hepatocarcinogenesis in transgenic Hbx mice 129,130 Overexpressed in liver cancer…”
Section: Cul4a Oncogenicmentioning
confidence: 99%
“…Lung cancer initiation and progression (transgenic overexpression of Cul4a) [89][90][91] ;Resistant to UV-induced skin carcinogenesis (skin-specific knockout of Cul4a) 55 Overexpressed in multiple myeloma 310 , cholangiocarcinoma 113,114 , gastric cancer [102][103][104] , colorectal cancer 104,[107][108][109] , ovarian cancer 104,112,311 , lung cancer 93,110,111 , breast cancer [104][105][106] , osteosarcoma 312,313 , hepatocellular cancer 117,314 , malignant pleural mesothelioma 315,316 , pituitary adenoma 317 , prostate cancer 318 CUL4B Oncogenic Spontaneous development of liver cancer (transgenic overexpression of Cul4b) 92 Overexpressed in cholangiocarcinoma 120 , pancreatic carcinoma 119 , lung cancer 93 • 118 , colorectal cancer 115,116 , glioma 319 , liver cancer 122 , cervical cancer 121 290,325 HBx Hepatocarcinogenesis in transgenic Hbx mice 129,130 Overexpressed in liver cancer…”
Section: Cul4a Oncogenicmentioning
confidence: 99%
“…[ 8 ] For example, CUL4A participates a role in the regulation of osteosarcoma and regulates the cell growth in osteosarcoma. [ 9 ] Besides, knockdown of CUL4A is able to suppress the invasive ability of osteosarcoma cells. [ 10 ] However, few studies have reported the role of CUL4A in osteoclast differentiation.…”
Section: Introductionmentioning
confidence: 99%